Asymptotic behavior of weakly dissipative Timoshenko system with internal constant delay feedbacks. Issue 1 (2nd January 2016) - Apalara, Tijani A.
Abstract : In this paper, we consider a one-dimensional Timoshenko system with a linear frictional damping and a constant delay acting on the displacement equation. Under appropriate assumptions on the weight of the delay and the wave speeds, we establish the well posedness and asymptotic stability results of the system. Our stability results show that the dissipation through the frictional damping is strong enough to uniformly stabilize the system even in the presence of delay.